2007
DOI: 10.1021/jp071942u
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Geometry and Magnetic Parameters of Fluorinated Radicals by Simulation of Powder ESR Spectra and DFT Calculations:  The Case of the Radical RCF2CF2 in Nafion Perfluorinated Ionomers

Abstract: The ESR spectrum of the chain-end radical RCF2CF2* detected in Nafion perfluorinated membranes exposed to the photo-Fenton reagent was accurately simulated by an automatic fitting procedure, using as input the hyperfine coupling tensors of the two F alpha and two F beta nuclei as well as the corresponding directions of the principal values from density functional theory (DFT) calculations. An accurate fit was obtained only for different orientations of the hyperfine coupling tensors for the two F alpha nuclei,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Our experiments suggest that sulphonate groups can also be attacked by Á OH radicals, possibly with different reaction rates, as was suggested in a recent paper by Zhou et al [89]. The observation of two radical adducts in the MC that mimics the Nafion side chain, PFEESA, may suggest that Nafion fragmentation can also take place in the side chain, both at the sulphonic groups and near the ether bond, as proposed in our previous papers [16,25]. The H 2 O 2 used here (38 mM) has a profound influence on the ultimately trapped species observed in our experiments.…”
Section: Relevance To Nafion Degradationsupporting
confidence: 81%
See 1 more Smart Citation
“…Our experiments suggest that sulphonate groups can also be attacked by Á OH radicals, possibly with different reaction rates, as was suggested in a recent paper by Zhou et al [89]. The observation of two radical adducts in the MC that mimics the Nafion side chain, PFEESA, may suggest that Nafion fragmentation can also take place in the side chain, both at the sulphonic groups and near the ether bond, as proposed in our previous papers [16,25]. The H 2 O 2 used here (38 mM) has a profound influence on the ultimately trapped species observed in our experiments.…”
Section: Relevance To Nafion Degradationsupporting
confidence: 81%
“…Based on the different F b hfs in Teflon and in Nafion, we have suggested that the radical in Nafion may be formed by degradation initiated near or at the side chain [16]. Additional support for this assignment has emerged recently, on the basis of fitting of the ESR spectrum and DFT calculations [25].…”
Section: Introductionmentioning
confidence: 94%
“…Accordingly, the fitting of hyperfine coupling tensors had to be done using numerical derivatives in the latter case; the fitting of the g-tensor and the line-width using analytical formulae (6) and (7) proceeded significantly faster. F 2 • radical [20] makes it difficult to obtain precise coupling values when the line-width is of comparable magnitude. A rather trivial condition to obtain accurate parameters by fitting is therefore that a change of the parameters should affect the shape of the spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that the radical detected by ESR in Nafion is of type ROCF 2 CF 2 d , which is formed by the action of oxygen radicals on the Nafion side chain. 119 Isotropic and anisotropic ESR spectra were recorded for the radical anions of hexafluorocyclobutene (c-C 4 F 6 À ), octafluorocyclopentene (c-C 5 F 8 À ) and perfluoro-2-butene (CF 3 CFQCFCF 3…”
Section: àDmentioning
confidence: 99%